Outcome and complications of operatively treated subaxial cervical spine injuries: A population-based retrospective cohort study - Joel Alve; Jukka Huttunen; Ville Leinonen; Henna-Kaisa Jyrkkänen; Nils Danner (World Neurosurgery: X, 2024)
Objective: The aim was to study the outcome and complications of operative treatment for subaxial cervical spine injuries with respect to injury morphology and surgical strategy. Methods: A population-based cohort of 271 consecutive patients treated at Kuopio University Hospital from 2003 to 2018 was retrospectively reviewed. Results: The mean age was 52.4 (range 12–90) years and 78.6% were male. The AOSpine morphological classification was C in 56.5%, B in 24.7% and A in 17.0% of cases. The surgical approach was anterior in 70.8%, posterior in 20.3% and combined in 8.9% of patients. Fixation alignment was maintained in 96.9% of patients. Instrumentation failures were observed only in patients operated anteriorly but no statistical difference was found between the surgical approaches. The American Spinal Injury Association Impairment Scale (AIS) grade improved in 22.1% of patients. Patients with preoperative AIS grade C had significant potential for neurological improvement (OR 10.44; 95% CI 1.77–61.56; p = 0.010). Postoperative, mostly mild, complications manifested in 22.5% of patients. The posterior approach was associated with fewer postoperative complications (OR 0.18; 95% CI 0.06–0.51; p = 0.001). Preoperative AIS grade A was a significant predisposing factor for complications (OR = 4.90; 95% CI = 1.49–16.10; p = 0.009). The perioperative (90-day) mortality rate was 3.3%. The mean follow-up period was 64.7 ± 25.9 (radiological)/136.7 ± 174.8 (clinical) days. Conclusions: Operative treatment is safe and effective but the surgical approach should be patient- and injury-specific. The prognosis for neurological recovery from spinal cord injury is superior in patients with partially preserved motor function.